2021
DOI: 10.1182/blood.2020009655
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genomic analyses of cutaneous T-cell lymphomas reveal the molecular bases for disease heterogeneity

Abstract: Cutaneous T cell lymphomas (CTCLs) are a clinically heterogeneous collection of lymphomas of the skin-homing T cell. To identify molecular drivers of disease phenotypes, we assembled a cohort of CTCLs with representative samples from diverse disease subtypes and stages. Via DNA/RNA-sequencing, immunophenotyping, and ex vivo functional assays, we identified the landscape of putative driver genes, elucidated genetic relationships between CTCLs across disease stages, and inferred molecular subtypes in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 47 publications
6
48
0
2
Order By: Relevance
“…However, even among studies showing overall similar PD‐1 expression levels, some have reported trends toward higher PD‐1 positivity in SS cases (Horna et al, 2019; Khodadoust et al, 2020; Wada et al, 2011). While it has been suggested that this difference in PD‐1 expression may reflect a differing underlying biology of these two entities (Cetinözman et al, 2012), a recent study demonstrated genetic commonalities between MF and SS, suggesting they may represent two extremes of the same disease (Park et al, 2021). This study also showed a correlation between lower‐level PD‐1 protein expression, a proliferative phenotype, and a high frequency of alterations of PDCD1 , the gene that encodes PD‐1, in MF and SS while higher level PD‐1 expression correlated with a non‐proliferative phenotype and a low frequency of PDCD1 alterations.…”
Section: Discussionmentioning
confidence: 99%
“…However, even among studies showing overall similar PD‐1 expression levels, some have reported trends toward higher PD‐1 positivity in SS cases (Horna et al, 2019; Khodadoust et al, 2020; Wada et al, 2011). While it has been suggested that this difference in PD‐1 expression may reflect a differing underlying biology of these two entities (Cetinözman et al, 2012), a recent study demonstrated genetic commonalities between MF and SS, suggesting they may represent two extremes of the same disease (Park et al, 2021). This study also showed a correlation between lower‐level PD‐1 protein expression, a proliferative phenotype, and a high frequency of alterations of PDCD1 , the gene that encodes PD‐1, in MF and SS while higher level PD‐1 expression correlated with a non‐proliferative phenotype and a low frequency of PDCD1 alterations.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the designation "MF with leukemic involvement" is recommended, although genetic features of both MF and SS have been recently described in patients with SS preceded by MF. 15…”
Section: Mycosis Fungoidesmentioning
confidence: 99%
“…The ISCL recommends that such cases be designated as SS preceded by MF or secondary erythrodermic CTCL Conversely, patients with MF, but without erythroderma, may meet hematologic criteria for SS. In these cases, the designation “MF with leukemic involvement” is recommended, although genetic features of both MF and SS have been recently described in patients with SS preceded by MF 15 …”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations